RANCANG BANGUN APLIKASI PERHITUNGAN RENCANA ANGGARAN BIAYA (RAB) PEMBANGUNAN RUMAH TINGGAL - Muhammad Ridwan; Sutardi Sutardi; Bambang Pramono; Laode Muh. Golok Jaya (semanTIK, 2018)
The Budget Plan is one of the main processes in a project because it is the basis for creating a budget framework to be issued. The Budget Plan is indispensable for calculating a building or project with the many costs required for materials and wages, as well as other costs associated with building or project implementation. For that required a careful calculations of the total cost of manufacture, volume of work, type of work, material prices and wage handyman in accordance with Indonesian National Standard (SNI).The results of research that has been done is an application that can facilitate user activity to plan the cost of housing construction. With the menus contained in this application can help users to prepare for the needs of what is needed if you want to build a residence such as materials, wage handyman and the price of materials. In addition, it can reduce the level of human error in the calculation of cost analysis needsKeywords— Homes, Budget Plan, PHP Programming. DOI : 10.5281/zenodo.1402404